ANALISIS PENGARUH PENYERAPAN KALOR TERHADAP EFISIENSI COOLING TOWER PADA TUNGKU INDUKSI PENGECORAN LOGAM DI POLMAN ASTRA - Komarudin Komarudin; Rudi Saputra; Satriyo Yudi Baskoro (Bina Teknika, 2017)
In the process of inducing metal, coil receives heat from the molten metal (molten). Therefore, it takes a cooling medium flowing in the coil casing and has a good conductivity. So here media of cooling tower water is used, so the water temperature can be maintained at the ambient air wet bulb temperature. With the optimal heat absorption cooling tower efficiency can be maintained. Besides, the material aluminum / molten can be melted well as the process of inducing metal running perfectly and there is no buildup of material on the walls of the furnace. With the application of a double pump with the series circuit to increase the water flow rate and can boost the absorption of the heat from the furnace wall and the pipe to the water coil.